Bauran Promosi, Lingkungan Internal Individu, Proses Pengambilan Keputusan Pembelian Pelanggan dan Loyalitas Pelanggan - Apri Budianto (Kontigensi : Jurnal Ilmiah Manajemen, 2015)
This study was conducted to contribute to the development of economic science, especially the promotion mix, the internal environment of individuals, the decision making process, customer loyalty, strategic management, marketing management, human resources management, and economics in general. Research carried out by using the method of survey and explanatory descriptive survey of customers minimarket with the large sample size of 400 people through simple random sampling technique proportionally. The method of analysis is structural equation model (SEM). The conclusion of this study were 1) Performance of the promotion mix used Priangan minimarket in the East Region according to the category of customer perceptions are interesting. 2) The customer's purchase decision based on customer perceptions Priangan minimarket in the East Region are in a strong category. 3) Customer loyalty minimarket in the Eastern Region Priangan based pyramid profitable customer loyalty / provide profit for the company (mini) starts from a client, customer advocate, and partner. 4) Mix of promotions and internal environment of an individual having a relationship (correlation) is positive but low. 5) Mix of campaign and individual internal environment affect customer buying decision process either partially or simultaneously.